2022
DOI: 10.3389/fendo.2022.1089419
|View full text |Cite
|
Sign up to set email alerts
|

The role of the renin-angiotensin system (RAS) in salinity adaptation in Pacific white shrimp (Litopenaeus vannamei)

Abstract: The renin-angiotensin system (RAS) is a hormonal system that plays an important role in the regulation of blood pressure and cardiovascular homeostasis in mammals. In fishes, the RAS pathway participates in osmoregulation and salinity adaptation. However, the role of the RAS pathway in invertebrates, particularly in crustaceans, remains unknown. In this study, four key genes of the RAS pathway (LV-ACE, LV-APN, LV-AT1R, and LV-RR) were cloned, characterized, and their expression levels were detected in the eyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In the similar with P. japonicus in salinity 37 and 21 ppt. and temperatures 10-14°C and 25°C, this research indicated the higher excretion of ammonia depended on high temperature and low salinity (Farhadi et al, 2022).…”
Section: Water Qualitymentioning
confidence: 56%
“…In the similar with P. japonicus in salinity 37 and 21 ppt. and temperatures 10-14°C and 25°C, this research indicated the higher excretion of ammonia depended on high temperature and low salinity (Farhadi et al, 2022).…”
Section: Water Qualitymentioning
confidence: 56%
“…Studies have shown that the expression of anthocyanin and rhodopsin genes can help shrimp to cope with salinity stress [ 23 ]. In addition, studies have shown that the renin-angiotensin system (RAS) plays important roles in salinity adaptation in Penaeus vannamei [ 24 ]. At present, there are more and more transcriptomic studies being conducted on the response of aquatic organisms to saline environments.…”
Section: Introductionmentioning
confidence: 99%